A PHILOSOPHICAL ANALYSIS OF THE CONCEPT OF ‘POLITICAL CULTURE’ (International journal of artificial intelligence, 2026)
This article analyzes the philosophical essence of the concepts of “culture” and “political culture,” their formation factors, and their role in the development of society. The nature of culture as a social phenomenon, its close connection with human activity, and its manifestation as a system of values are revealed. In addition, the structural elements of political culture, its relationship with citizens’ political consciousness and behavior, and its importance in the development of a democratic society are examined from a philosophical perspective. Special attention is given to the issues of enhancing political culture in modern society.